Green Accounting and Environmental Performance on Financial Performance: Strategic Insights from the Mining Industry in Indonesia - Aulia, Azwani; Siahaan, Magda; Siregar, Johannes Kristian (CV. Science Tech Group, 2025)
The increasing degradation of the environment and growing demand for sustainability have shifted the paradigm in assessing corporate performance. Sustainability has three dimensions beyond profit, called the triple bottom line. The mining sector has critical strategic significance for economic growth, although entwined with high environmental hazards. Using EViews tool, this study explores green accounting and environmental performance's impact on financial performance of the business. Despite being based on data from financial statements, annual and corporate sustainability reports, the results are of paramount importance and read like this. These studies show that environmental performance has a strong and positive impact on financial performance, confirming the financial relevance of sustainability initiatives. In contrast, green accounting methods have no significant effects on financial results, indicating a disconnect between conventional accounting scopes and viable eco-initiatives. Collectively, these factors have a material impact on corporate performance. The research sectoral focus and sample confines its generalisability. Future studies need to explore intervening or moderating models and incorporate further variables in order to deepen understanding and broaden applicability. Our study adds to the existing literature debates about how environmental sustainability can be reconciled with corporate financial performance.